Sorption isotherms and isosteric heats of sorption of Malaysian paddy - Mousa, Wael; Mohamad Ghazali, Farinazleen; Selamat, Jinap; Mohd Ghazali, Hasanah; Radu, Son (Springer, 2014)
Understanding the water sorption characteristics of cereal is extremely essential for optimizing the drying process and ensuring storage stability. Water relation of rough rice was studied at 20, 30, 40 and 50 °C over relative humidity (RH.) between 0.113 and 0.976 using the gravimetric technique. The isotherms displayed the general sigmoid, Type II pattern and exhibited the phenomenon of hysteresis where it was more pronounced at lower temperatures. The sorption characteristics were temperature dependence where the sorption capacity of the paddy increased as the temperature was decreased at fixed (RH). Among the models assessed for their ability to fit the sorption data, Oswin equation was the best followed by the third order polynomial, GAB, Smith, Chung-Pfost, and Henderson models. The monolayer moisture content was higher for desorption than adsorption and tend to decrease with the increase in temperature. Given the temperature dependence of the sorption isotherms the isosteric heats of sorption were calculated using Claussius-Clapeyron equation. The net isosteric heats decreased as the moisture content was increased and heats of desorption were greater than that of adsorption.